Association of Gender, Diagnosis, and Obesity With Retention Rate of Secukinumab in Spondyloarthropathies: Results Form a Multicenter Real-World Study - García-Dorta, Alicia; León-Suarez, Paola; Peña, Sonia; Hernández-Díaz, Marta; Rodríguez-Lozano, Carlos; González-Dávila, Enrique; Hernández-Hernández, María Vanesa; Díaz-González, Federico (Frontiers in Medicine, 2022)
Background: Secukinumab has been shown effective for psoriatic arthritis (PsA) and axial spondylarthritis (AxSpA) in randomized trials. The aim of this study was to analyze baseline patient and disease characteristics associated with a better retention rate of secukinumab under real-world conditions. Patients and methods: Real-life, prospective multicenter observational study involving 138 patients, 61 PsA and 77 AxSpA, who were analyzed at baseline, 6, 12 months and subsequently every year after starting secukinumab regardless of the line of treatment. Demographics and disease characteristics, measures of activity, secukinumab use, and adverse events were collected. Drug survival was analyzed using Kaplan-Meier curves and factors associated with discontinuation were evaluated using Cox regression. The machine-learning J48 decision tree classifier was also applied. Results: During the first year of treatment, 75% of patients persisted with secukinumab, but accrued 71% (n=32) in total losses (n=45). The backward stepwise (Wald) method selected diagnosis, obesity, and gender as relevant variables, the latter when analyzing the interactions. At 1 year of follow-up, the Cox model showed the best retention rate in the groups of AxSpa women (95%, 95%CI 93-97%) and PsA men (89%, 95%CI 84-93%), with the worst retention in PsA women (66%, 95%CI 54-79%). The J48 predicted secukinumab retention with an accuracy of 77.2%. No unexpected safety issues were observed. Conclusions: Secukinumab shows the best retention rate at 1 year of treatment in AxSpA women and in PsA men, independently of factors such as the time of disease evolution, the line of treatment or the initial dose of the drug.